Environmental oriented corporate social responsibility and customer loyalty: corporate image as a mediator / Nor Irwani Abdul Rahman - Abdul Rahman, Nor Irwani (2015)
Malaysian retailers are faced with intense competition and increasing demand from customers. Thus, they need to understand the determinants that influence customer loyalty in order to maintain their competitiveness. Given that situation, this study attempts to contribute in academic field by using environmental oriented CSR as a determinant to customer loyalty with corporate image as a mediator. Three theories were utilized to explain the study framework namely Stakeholder Theory, Organizational Identification Theory and System Theory. The objective of this study is to examine the relationship between environmental-CSR and customer loyalty while mediated by corporate image. Using hierarchical multiple regression analysis, the result show that two dimensions namely social and community involvement and customer are found to have significant relationship with customer loyalty mediated by corporate image. A total of 400 customers from hypermarkets located at Klang Valley in Malaysia were participated as respondents. Data for all the study variables have been collected through self-administered questionnaires. Thus the result of this study supports the objectives of this study. Overall, the results indicate that the framework provides a good understanding of the factors that influence customer loyalty. The findings also can be use to solidify the notion that being committed to environment and sustainability issues is not just a public relation exercise, but having long-term and positive bottom-line benefits